Environment and Environmental Policy - Djeghri, Lamia (Journal of Human Sciences, 2022)
The subject of environmental protection is of great importance because of the importance it represents for the existence and survival of man and the living organism that surrounds him and their survival for generations. future, therefore, international efforts are combined to protect the environment from the phenomenon of pollution, which represents the most dangerous thing that can threaten the ecological balance, and this is called the science of environment and environmental policy, because to solve the many obstacles that affect the environment we must specify the definition of the environment and the environmental system that depends on the definition of the Environmental Policy, which in turn is based on the planning to preserve environmental resources during the stages of production, consumption, to protect the environmental balance.